2012
DOI: 10.1136/emermed-2011-200496
|View full text |Cite
|
Sign up to set email alerts
|

Are boys and girls that different? An analysis of traumatic brain injury in children

Abstract: IntroductionThe Phillips Report on traumatic brain injury (TBI) in Ireland found that injury was more frequent in men and that gender differences were present in childhood. This study determined when gender differences emerge and examined the effect of gender on the mechanism of injury, injury type and severity and outcome.MethodsA national prospective, observational study was conducted over a 2-year period. All patients under 17 years of age referred to a neurosurgical service following TBI were included. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…is finding is in agreement with Nigerian, South African, and Tunisian studies. is could be related to boy's risk-prone behavior resulting in high energy transfer and their outdoor engagement [14,30,[34][35][36][37]. Concerning mechanisms of injury, unintentional pedestrian RTA and falls were the most common causes followed by intentional fights/violence injuries.…”
Section: Discussionmentioning
confidence: 99%
“…is finding is in agreement with Nigerian, South African, and Tunisian studies. is could be related to boy's risk-prone behavior resulting in high energy transfer and their outdoor engagement [14,30,[34][35][36][37]. Concerning mechanisms of injury, unintentional pedestrian RTA and falls were the most common causes followed by intentional fights/violence injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many neuroanatomical regions involved in social cognition are sexually dimorphic, including septal and hypothalamic nuclei, and components of the circuitry involved in behavioral motivation (Kim et al, 2015; Shah et al, 2004). The degree to which these sexual distinctions influence behavioral outcomes after TBI is uncertain, although there is evidence of differential psychosocial and communication problems in male versus female patients (Despins et al, 2015; Gerring et al, 2002; Moreno and McKerral, 2015; Scott et al, 2015), even in young children (Collins et al, 2013; Kaldoja and Kolk, 2015). Further studies are needed in this arena, as sex differences in how the developing brain responds to pTBI may have important implications for both diagnosis and treatment after pTBI.…”
Section: Moving Forward: Delineating Potential Biological Mechanismsmentioning
confidence: 99%
“…For example, expectations and assumptions that boys should or will engage in more risk-taking behavior than girls can result in boys actually engaging in more risk-taking behavior. Additionally, Collins et al (2013) found that boys age 0-17 years were more likely to engage in high intensity risk-taking behaviors and less likely to use protective equipment during these behaviors compared to girls. Motivation for engaging in such behaviors without the use of protection equipment may stem from the perception that "boys are tough," and should ignore the ramifications of injury.…”
Section: Introductionmentioning
confidence: 97%